2004
DOI: 10.1111/j.1365-2125.2004.02095.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regular consumption of grapefruit juice on the pharmacokinetics of simvastatin

Abstract: AimsSimvastatin, a substrate for CYP3A4, is extensively metabolized during the first pass. Our aim was to investigate the effect of regular consumption of g rapefruit juice on the pharmacokinetics of simvastatin. MethodsIn a randomized cross-over study with two phases, 10 healthy volunteers ingested grapefruit juice 200 ml or water (control) for 3 days. On day 3, a single 40-mg dose of simvastatin was administered with grapefruit juice 200 ml or water. Plasma concentrations of simvastatin and simvastatin acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
74
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 19 publications
10
74
0
1
Order By: Relevance
“…Several studies have shown that grapefruit juice elevates the blood levels of some orally taken drugs, primarily by inhibiting intestinal CYP3A4-mediated first-pass metabolism (Fuhr et al 2002;Dahan & Altman, 2004;Lilja et al 2004;Paine et al 2004Paine et al , 2005, CYP3A4 being a type of cytochrome P450. These studies suggest a potential therapeutic benefit from using the active constituents of grapefruit to increase drug bioavailability.…”
mentioning
confidence: 99%
“…Several studies have shown that grapefruit juice elevates the blood levels of some orally taken drugs, primarily by inhibiting intestinal CYP3A4-mediated first-pass metabolism (Fuhr et al 2002;Dahan & Altman, 2004;Lilja et al 2004;Paine et al 2004Paine et al , 2005, CYP3A4 being a type of cytochrome P450. These studies suggest a potential therapeutic benefit from using the active constituents of grapefruit to increase drug bioavailability.…”
mentioning
confidence: 99%
“…This effect is present whether grapefruit is taken as a whole fruit or in juice form, causing clinically relevant increase in blood concentration of affected drugs that can result in adverse effects. 170 Some examples include exaggerated antihypertensive response with calcium channel blockers (felodipine), 171 increased risk of rhabdomyolysis and hepatotoxicity with statins, 168 hypoglycemia with antidiabetics (repaglinide), increased steady-state concentration of cyclosporine, potentiation of toxicity with antiarrhythmics with QT prolongation and torsades de pointes, 172 and augmentation of antiplatelet activity of cilostazol leading to pupura. 173 There also are case reports of elevated INR and hematoma with grapefruit juice ingestion in patients previously stabilized on warfarin.…”
Section: Grapefruit Juicementioning
confidence: 99%
“…Even a single exposure to one glass of the grapefruit juice can produce clinically significant interaction, and with the half-life of CYP3A4 being > 8 hours, its reversal inhibition by grapefruit increases the bioavailability and blood levels of drugs metabolized by this enzyme (Table 3) up to 72 hours. 168,169 Therefore, repeated juice intake can result in adverse effects even if not taken concomitantly with drugs. This effect is present whether grapefruit is taken as a whole fruit or in juice form, causing clinically relevant increase in blood concentration of affected drugs that can result in adverse effects.…”
Section: Grapefruit Juicementioning
confidence: 99%
“…The literature has reported drug-drug interactions between lovastatin and drugs or related products with effect on drugs such as colesevelam, gemfibrozil, itraconazole or dietary supplements determined via pharmacokinetic studies [10][11][12][13][14][15]. Berberine is an alkaloid available from the medicinal plant Coptis chinensis that is widely used clinically in the treatment of gastrointestinal infections, diabetes, hypertension, and hypercholesterolemia.…”
Section: Introductionmentioning
confidence: 99%
“…In the in vitro HepG2 cells experiments, berberine could increase the metabolic activity by increasing the metabolic parameters of CL, which was increased from 1.06 to 1.48 mL/10 5 (cell)·h −1 with the induction of berberine, the Km was increased three times in berberine induced group as well, which was compliance with the obtained pharmacokinetics parameter from AUC0-12 of lovastatin decreased 2.5 times (approximately three times). The literature has reported drug-drug interactions between lovastatin and drugs or related products with effect on drugs such as colesevelam, gemfibrozil, itraconazole or dietary supplements determined via pharmacokinetic studies [10][11][12][13][14][15]. Berberine is an alkaloid available from the medicinal plant Coptis chinensis that is widely used clinically in the treatment of gastrointestinal infections, diabetes, hypertension, and hypercholesterolemia.…”
Section: Introductionmentioning
confidence: 99%